2018
DOI: 10.1111/eos.12564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sleep bruxism duration on perceived sleep quality in middle‐aged subjects

Abstract: Sleep-related bruxism may directly impact sleep quality. This study aims to evaluate potential relationships between sleep bruxism events and related daytime symptoms. We investigated 22 patients (42.1 ± 11.6 yr of age) with sleep bruxism in comparison with 12 good sleeper control subjects of similar age (41.0 ± 11.5 yr). Sleep bruxism was visually analyzed and categorized according to sleep stage, bruxism type (tonic/phasic) and duration. Clinical instruments comprised the Epworth Sleepiness, the Brugmann Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
13
1
3
Order By: Relevance
“…In terms of SE, there were no differences between the SSB and MSB groups and the CG, which is consistent with most previous studies (Kishi et al, 2020;Lavigne et al, 1996Lavigne et al, , 2002Macaluso et al, 1998). In two of the previous studies (Kishi et al, 2020;Macaluso et al, 1998), both healthy and control participants presented SE above 85%, but the CG participants had significantly higher mean values than those with bruxism (Neu et al, 2018;Palinkas et al, 2017;Yoshida et al, 2017). According to Neu et al (2018), this difference might be explained by the fact that participants with OSA were not excluded from their study, and the study group presented a higher mean AHI than that of control participants (AHI in SB was above 5, which suggests the presence of at least mild OSA).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of SE, there were no differences between the SSB and MSB groups and the CG, which is consistent with most previous studies (Kishi et al, 2020;Lavigne et al, 1996Lavigne et al, , 2002Macaluso et al, 1998). In two of the previous studies (Kishi et al, 2020;Macaluso et al, 1998), both healthy and control participants presented SE above 85%, but the CG participants had significantly higher mean values than those with bruxism (Neu et al, 2018;Palinkas et al, 2017;Yoshida et al, 2017). According to Neu et al (2018), this difference might be explained by the fact that participants with OSA were not excluded from their study, and the study group presented a higher mean AHI than that of control participants (AHI in SB was above 5, which suggests the presence of at least mild OSA).…”
Section: Discussionsupporting
confidence: 90%
“…In two of the previous studies (Kishi et al, 2020;Macaluso et al, 1998), both healthy and control participants presented SE above 85%, but the CG participants had significantly higher mean values than those with bruxism (Neu et al, 2018;Palinkas et al, 2017;Yoshida et al, 2017). According to Neu et al (2018), this difference might be explained by the fact that participants with OSA were not excluded from their study, and the study group presented a higher mean AHI than that of control participants (AHI in SB was above 5, which suggests the presence of at least mild OSA). In our study, the duration of sleep was unaffected by SB and no differences were found between groups in terms of TST, which is also consistent with most previous studies (Kishi et al, 2020;Lavigne et al, 2002;Lavigne et al, 1996;Macaluso et al, 1998;Neu et al, 2018;Yoshida et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Le syndrome des MPJ est lui caractérisé par des mouvements ou myoclonies récurrentes des jambiers au cours du sommeil, objectivable uniquement à la polysomnographie 16 Le bruxisme (contractions involontaires et rythmiques de la musculature masticatoire) lié au sommeil est un autre trouble moteur fréquent dont la prévalence peut atteindre 8 à 9 % dans la population générale (indépendamment du sexe). Il a été démontré que la durée cumulée de ces manifestations musculaires peut être associée à de la fatigue diurne et avoir des répercussions sur la qualité de sommeil perçue 39 . La PSG est communément considérée l'outil " gold standard " pour la mise au point diagnostique du bruxisme, étant donné que seule une PSG permet une évaluation quantitative et qualitative complète et objective du bruxisme durant le sommeil 39 .…”
Section: Les Mouvements Anormaux En Relation Avec Le Sommeilunclassified
“…Il a été démontré que la durée cumulée de ces manifestations musculaires peut être associée à de la fatigue diurne et avoir des répercussions sur la qualité de sommeil perçue 39 . La PSG est communément considérée l'outil " gold standard " pour la mise au point diagnostique du bruxisme, étant donné que seule une PSG permet une évaluation quantitative et qualitative complète et objective du bruxisme durant le sommeil 39 .…”
Section: Les Mouvements Anormaux En Relation Avec Le Sommeilunclassified